Ocean temperature variability for the past 60 years on the Norwegian-Svalbard margin influences gas hydrate stability on human time scales - Ferré, Bénédicte; Mienert, Jürgen; Feseker, Tomas (Journal of Geophysical Research: Oceans, 2012)
The potential impact of future climate change on methane release from oceanic gas hydrates is the subject of much debate. We analyzed World Ocean Database quality controlled data on the Norwegian‐Svalbard continental margin from the past 60 years to evaluate the potential effect of ocean temperature variations on continental margin gas hydrate reservoirs. Bottom water temperatures in the Norwegian‐Svalbard margin were subject to significant cooling until 1980 (by ∼2°C offshore NW‐Svalbard and in the Barents Sea) followed by a general bottom water temperature increase until 2010 (∼0.3°C in deep‐water areas offshore NW‐Svalbard and mid‐Norwegian margin and ∼2°C in the shallow areas of the Barents Sea and Prins Karls Forland). Bottom water warming in the shallow outer shelf areas triggered the Gas Hydrate Stability Zone (GHSZ) retreat toward upper continental slope areas, potentially increasing methane release due to gas hydrate dissociation. GHSZ responses to temperature changes on human time scales occur exclusively in shallow water and only if near‐surface gas hydrates exist. The responses are associated with a short time lag of less than 1 year. Temperatures in the bottom water column seem to be partly regulated by the North Atlantic Oscillation (NAO), with positive NAO associated with warm phases. However, cooling events in the surface water offshore NW‐Svalbard might be associated with El Niño events of 1976–1977, 1986–1987 and 1997–1998 in the Pacific. Such ocean cooling, if long enough, may delay ocean temperature driven gas hydrate dissociation and potential releases of methane to the ocean. Key Points Increasing seabed temperatures makes gas hydrate unstable in shallow regions Temperature increase in deep areas is not enough to destabilize gas hydrate Bottom water temperature seems to be partly regulated by the NAO